Readability of a Translated Nazam Text: The Case of Tafsīriyah Muqaddimah Jazariyah in Arabic Language Pedagogy - Salsabila, Shafa; Supriadi, Rinaldi (IAIN Madura, 2026)
Readability research has largely focused on prose-based texts, leaving translated nazam materials in Arabic language pedagogy underexplored. This study investigates the readability of the Indonesian translation module of Tafsīriyah Muqaddimah Jazariyah by Abu Ezra al-Fadhli within the framework of Arabic language pedagogy. Using a qualitative descriptive approach, three discourse samples from the beginning, middle, and end sections of the module were analyzed through the Gunning Fog Index as a heuristic tool to assess linguistic load based on sentence length and lexical density. The results show an average Fog Index score of 6.08, indicating that the module is generally categorized as easy to read, although variations in readability appear across sections. The findings demonstrate that sentence structure plays a more significant role in pedagogical accessibility than lexical complexity alone. This study highlights the need to interpret readability formulas critically when applied to translated nazam texts and contributes to a genre-sensitive understanding of readability in Arabic instructional materials.